PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN DENGAN KEPUASAAN KERJA SEBAGAI MEDIASI PADA PT. SENATOR INTERNASIONAL INDONESIA - Sitio, Vera Sylvia Saragi (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
There are various efforts need to be made by the company in dealing with its competitors. One of the efforts made is to prepare resources that have competence and quality so as to improve employee performance. Total Quality Management (TQM) is a concept of maximizing organizational competitiveness through continuous improvement. This study aims to determine the effect of Total Quality Management on performance through job satisfaction as a mediating variable. The population is 69 people. This study used a purposive sampling technique of 47 people. The analysis technique used is descriptive path (Path Analysis) SPSS computer program version 24 for Mac. The results of this study indicate there is an effect of TQM on employee performance mediated by job satisfaction with a magnitude of influence of 89.2%. The path analysis results show that the direct effect of TQM on employee performance is smaller than the indirect effect of TQM on employee performance through job satisfactionKeywords: Total Quality Management, Job Satisfaction, Employee Performance